L'evoluzione delle ortofotocarte (GEOmedia, 2010)
The evolution of orthophotomapsOrhophotomaps are about half a century old, although the technique today is completely different to fifty years ago. In this article a short history of orthophotomaps is exposed and commented. The method for preparing digital orthophotos and particularly of ‘true-orthophoto' is also presented. In Italy orthophotos are somewhat diffused, mainly as technical maps ofregions as well for the local use in the municipalities. Unfortunately the way these maps are compiled is not regulated in Italy.